THEORETICAL STUDY RELATED TO THE FACTORS OF RELIGION CONFLICT IN THE COMMUNITY - H. M. Tamsir Ridho, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The emergence of one group's stereotype against other groups of different religions usually triggers the conflict between religious community followed by effort to attack each other, to kill each other, to burn houses of worship and places of value of each religion. Referring to the explanation above, this article analyzes the background factors that make the occurrence of religious conflict in the community. The results of the study of the literature review can be concluded that religious conflict was a form of dispute or conflict between individuals or groups in society. This contradiction can involve two people or many people in social movement, group interest, class, gender, organization, political party, ethnicity, race or religion, and other interest. Factors causing religious conflict were the existence of truth claims by individuals or certain groups that increasingly makes blurred (biased) between religious area and tribal area, wrong understanding related to jihad due to radicalism doctrine and understanding, lack of religious tolerance and lack of pluralism ideology understanding. Then the issues that have the potential to cause conflict are related to moral issues, sectarian issues, communal issues, terrorism issues, religious-political issues, and other issues.